Design and performance of a novel neutron powder diffractometer: PEARL at TU Delft. Issue 5 (4th August 2016) - van Eijck, L.; Cussen, L. D.; Sykora, G. J.; Schooneveld, E. M.; Rhodes, N. J.; van Well, A. A.; Pappas, C.
Abstract : This manuscript describes the novel neutron powder diffractometer PEARL at Delft University of Technology and shows the first experimental results. Abstract : The performance of the new neutron powder diffraction instrument PEARL that is installed at the research reactor of Delft University of Technology is reported. It is based on the optimization concepts developed by Cussen [ Nucl. Instrum. Methods Phys. Res. Sect. A (2007), 583, 394–406], which lead to high performance competing with existing constant‐wavelength neutron powder diffractometers, despite the relatively low source brightness of the 2 MW reactor of Delft University of Technology.